2019
DOI: 10.1002/advs.201900034
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic, Evolutionary, and Mechanistic Study of MCR‐5 Action Suggests Functional Unification across the MCR Family of Colistin Resistance

Abstract: A growing number of mobile colistin resistance (MCR) proteins is threatening the renewed interest of colistin as a “last‐resort” defense against carbapenem‐resistant pathogens. Here, the comparative genomics of a large plasmid harboring mcr‐5 from Aeromonas hydrophila and the structural/functional perspectives of MCR‐5 action are reported. Whole genome sequencing has identified the loss of certain parts of the Tn 3 ‐type transposon typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 72 publications
1
42
0
1
Order By: Relevance
“…Also, we are concerned with the appearance of new tet(X) variants and its expanded dissemination in the near future. Retrospectively, a similar scenario is seen with the MCR family of polymyxin resistance [12][13][14]. Not only have the new mcr variants already been extended from mcr-1 [1,14,15] to mcr-9 [16,17], but also some of them, like mcr-1 [1,12] and mcr-3 [1,18], have disseminated globally.…”
Section: Introductionmentioning
confidence: 74%
“…Also, we are concerned with the appearance of new tet(X) variants and its expanded dissemination in the near future. Retrospectively, a similar scenario is seen with the MCR family of polymyxin resistance [12][13][14]. Not only have the new mcr variants already been extended from mcr-1 [1,14,15] to mcr-9 [16,17], but also some of them, like mcr-1 [1,12] and mcr-3 [1,18], have disseminated globally.…”
Section: Introductionmentioning
confidence: 74%
“…The global spread of carbapenem‐resistant Enterobacteriaceae (CRE), including Escherichia coli , Klebsiella pneumoniae , and Salmonella is a serious threat to public health. Colistin was considered one of the last lines of defense against lethal CRE infections 1–5. Unfortunately, many species of Enterobacteriaceae are becoming increasingly resistant to colistin 2,4,6,7.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many species of Enterobacteriaceae are becoming increasingly resistant to colistin 2,4,6,7. One colistin resistant mechanism is the modification of Lipid A of LPS, catalyzed by the chromosome encoded machinery in Klebsiella pneumoniae , the LptA (EptA) in Neisseria , or mobile colistin resistance mcr‐1 in Enterobacteriaceae 5,8–11. Since its discovery in China, mcr‐1 resistance was reported in several other countries spanning six continents 5–7,12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations constitute a structural paradigm for understanding the mechanism of action for MCR family proteins, informing the design of inhibitors to bypass colistin resistance. In addition, the results of many evolutionary, genomic, and mechanistic studies have suggested that MCR members are functional, unified, and equivalent Zhang et al 2019a;Zhang et al 2019b;Zhang et al 2019c). Because the MCR-1-encoding gene appears to be the most prevalent protein having been detected in nearly 50 countries across 6 continents, as well also the most studied, we primarily focused on MCR-1 in the following discussion (Falgenhauer et al 2016;McGann et al 2016;Poirel et al 2017;Schwarz and Johnson 2016;Sun et al 2018).…”
Section: Introductionmentioning
confidence: 99%